Multimedia monster [supercomputer on a single chip]. - Moore, S.K (IEEE spectrum)
This paper presents a microprocessor jointly developed by IBM, Sony, and Toshiba, called Cell Broadband Engine Architecture (Cell). Originally conceived to power Sony's third-generation game console, the Playstation 3, Cell is a combination of general-purpose and multimedia processors. It defies an exact comparison with upcoming chips, but it's thought to be more powerful than the chips driving competing game systems. Cell can calculate at a blazing speed, in part, because it's made up of nine processors on a single chip of silicon, optimized for the kind of real-time calculations needed in today's broadband, media-rich environment. A specially designed 300-gigabit-per-second bus knits the processors into a single machine, and interface technology gives it fast access to memory and other off-chip systems.